The Opportunities and Challenges of Inclusive Education: Centring Student Voice in Irish Primary Schools - Stynes, Rosemarie (Trinity College Dublin. School of Education. Discipline of Education, 2025)
This study explores inclusive education, with a particular focus on the voice of the child. It investigates how children's voices are heard, acknowledged and facilitated as part of inclusive practice in a sample of Irish primary schools. The study examines the perspectives of inclusive education in these schools and, finally, considers the effect of leadership on inclusive education and the enabling of student voice. Student voice is central to meaningful inclusion. It ensures that children are actively involved in shaping their learning experiences, which allows teaching, support and policies to be adapted to meet the needs of the children rather than the other way round. When children's perspectives are listened to and valued, schools move beyond tokenistic inclusion towards meaningful participation, allowing barriers to participation, which may not be apparent to adults, to be removed. Listening to the voice of the child fosters a sense of belonging, agency and empowerment, all of which are key elements of inclusive education. The enabling of student voice allows the insights of children to influence and shape schools' culture and practice. To carry out the research, a mixed methods, multiple case study design, incorporating methodological triangulation and a participatory research element, was used. It consisted of a review of literature in the areas of inclusive education, student voice and leadership in schools. In each case study school, two focus group interviews were held with two groups of approximately five children, some with additional educational needs (AEN) and some without. Artwork was gathered from the children participating in the focus groups, portraying their images of a school they would like to attend and a school they would not like to attend. Separate, semi-structured interviews were held with the principal and the Special Educational Needs Co-ordinator (SENCo) of each school. Questionnaires were issued to all teachers and members of the Board of Management (BoM). A focus group interview was held in each school with four parents of children with AEN. A document analysis was carried out on relevant documents pertaining to each school to gain a clearer contextual understanding of each one's policies and procedures. In addition, a Children's Research Advisory Group (CRAG) was formed. The CRAG helped to design the questions used in the children's focus groups and also the interpretation and analysis of the data garnered from those focus groups. This study indicates that student voice enables children to feel included and valued, enhancing their self-esteem and academic engagement. It also promotes empathy and peer collaboration. Currently, student voice is heard through conventional democratic streams such as the Student Council. While student voice tends to focus on non-academic issues, it does not feature strongly at classroom level or concerning teaching and learning. There is a further challenge for the voice of the child to be heard and acted upon in a meaningful way when the child has AEN. Teachers' perspectives show a willingness and openness to inclusive education and to hear, acknowledge and facilitate student voice, and an acknowledgement that it can benefit all children, not just those with AEN. However, there is a limited availability of continuing professional development and resources, which undermines confidence among teachers. Large class sizes make differentiation difficult, and teachers find it challenging to balance individual children's needs with curriculum demands due to a lack of support teachers, time and other resources. Parents of children with AEN feel they are mostly supported by their school. However, they endure a battle to access resources to which their children should be automatically entitled. Effective school leadership is essential to foster an inclusive school culture and enable the voice of the child to be heard. The study recognises the importance of the role of the principal and SENCo in each school to build and develop rapport and relationships with stakeholders across the board. Despite it being a small-scale study, its focus on three separate contexts allows the results to be of greater practical value than they might otherwise be. This study has significant implications for policy and practice. Firstly, it addresses an important gap in the Irish education system by exploring not only how inclusion is perceived and put into practice but also how actively student voice is enabled in inclusive practices in these schools. While previous research has examined inclusion policies, student voice and leadership separately, few studies have explored the intersection of inclusive education, student voice and leadership in the context of Irish primary schools. Additionally, the inclusion of a CRAG aligns with participatory research principles, ensuring that the perspectives of children are not only studied but actively incorporated into the research process. This study has the potential to contribute to educational policy and practice, providing insights that can profitably inform teacher training, leadership development, and opportunities for meaningful student engagement and participation in Irish primary schools.
APPROVED
Keywords: inclusive education; student voice; leadership; Irish primary schools; additional educational needs (AEN); social constructivism; multiple case study; children's research advisory group (CRAG)